Respuesta :

Answer:

x=0,-1 and x=

​ x=\frac{2+\sqrt{10}}{3},\frac{2-\sqrt{10}}{3}x=

​3

​​  

​​  

Step-by-step explanation:

1 Cancel 2 on both sides.

3{x}^{2}+3x=03x

​2

​​ +3x=0

2 Factor out the common term 3x3x.

3x(x+1)=03x(x+1)=0

3 Solve for xx.

x=0,-1x=0,−1

1 Move all terms to one side.

3{x}^{2}-3x-1-x-1=03x

​2

​​ −3x−1−x−1=0

2 Simplify  3{x}^{2}-3x-1-x-13x

​2

​​ −3x−1−x−1  to  3{x}^{2}-4x-23x

​2

​​ −4x−2.

3{x}^{2}-4x-2=03x

​2

​​ −4x−2=0

3 Use the Quadratic Formula.

x=\frac{4+2\sqrt{10}}{6},\frac{4-2\sqrt{10}}{6}x=

​6

​4+2√

​10

​​  

​​ ,

​6

​4−2√

​10

​​  

​​  

4 Simplify solutions.

x=\frac{2+\sqrt{10}}{3},\frac{2-\sqrt{10}}{3}x=

​3

​2+√

​10

​​  

​​ ,

​3

​2−√

​10

​​  

​​  

ACCESS MORE